Beyond Personal Data Protection: Constructing a Legal Framework for Big Data Governance in Uzbekistan - Sarvar Zafarovich Tojiboyev; Dilfuza Ismailovna Imamova; Bobur Umidjon ugli Koryogdiev; Adolat Fakhriddin kizi Settieva; Ismigul Farkhod kizi Kubaeva (Contrarius Indonesia, 2026)
Advances in data analytics, artificial intelligence, and digital technologies have intensified legal challenges related to data governance, privacy, and accountability. However, Uzbekistan's legal framework remains insufficient to regulate Big Data, particularly concerning inferred data, profiling practices, and automated decision-making activities. This study aims to analyze the legal nature of Big Data, identify regulatory gaps in Uzbekistan’s legal framework, and develop a Big Data Governance Framework. The research employs normative legal research using statutory, conceptual, and comparative approaches. The findings reveal that first, the study establishes that Big Data represents a distinct legal phenomenon that differs from traditional legal concepts of personal data, databases, and intellectual property rights. Second, the study identifies substantial regulatory deficiencies within Uzbekistan's legal framework, including the absence of a clear legal definition of Big Data, fragmented regulatory arrangements, insufficient protection against profiling and secondary data use, limited algorithmic accountability, and weak institutional governance. Third, the study formulates a comprehensive Big Data Governance Framework that recognizes the legal status of Big Data, safeguards inferred data, strengthens the rights of data subjects, introduces Big Data Impact Assessment mechanisms, promotes algorithmic accountability, enhances institutional oversight, and integrates privacy rights, digital rights, and civil liability principles.